2018
DOI: 10.1590/s1980-6574201800020004
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of neurofunctional versus resistance training in improving gait and quality of life among patients with Parkinson’s disease: a randomized clinical trial

Abstract: Aims: to compare the efficacy of neurofunctional training versus resistance training in improving gait and quality of life among patients with PD. Methods: This randomized controlled trial included 40 participants randomly assigned to two groups through random number table generator: resistance training (RT) (n=19) and neurofunctional training (NT) (n=21). The RT group performed resistance exercises emphasizing the lower limbs and trunk, while the NT group sessions were focused on gait, functional independence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 36 publications
0
3
0
4
Order By: Relevance
“…Após o treinamento com esses exercícios, houve uma melhora nos parâmetros: velocidade da marcha [17,19,31], comprimento da passada [24,31], cadência [24,31] e comprimento do passo [19]. Do mesmo modo, os exercícios de resistência também estiveram presentes em quatro estudos [32,35,36,40]. Observou-se que na maioria dos protocolos os exercícios envolviam os principais grupos musculares dos membros inferiores [36], tronco e, ainda, membros superiores [32,35,40].…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Após o treinamento com esses exercícios, houve uma melhora nos parâmetros: velocidade da marcha [17,19,31], comprimento da passada [24,31], cadência [24,31] e comprimento do passo [19]. Do mesmo modo, os exercícios de resistência também estiveram presentes em quatro estudos [32,35,36,40]. Observou-se que na maioria dos protocolos os exercícios envolviam os principais grupos musculares dos membros inferiores [36], tronco e, ainda, membros superiores [32,35,40].…”
Section: Discussionunclassified
“…Do mesmo modo, os exercícios de resistência também estiveram presentes em quatro estudos [32,35,36,40]. Observou-se que na maioria dos protocolos os exercícios envolviam os principais grupos musculares dos membros inferiores [36], tronco e, ainda, membros superiores [32,35,40]. Em relação ao número de séries e repetições descritas pelos estudos, notou-se que apenas um trabalho não trouxe essas informações, já nos outros três estudos, utilizaram-se somente 2 séries e o número de repetições variou entre 8 e 20 repetições, alguns exercícios envolveram a extensão de joelho, quadril, tríceps [32] e flexão de joelho [36].…”
Section: Discussionunclassified
See 2 more Smart Citations
“…We screened all of these records and excluded 56 based on titles and abstracts, leaving 475 articles for full-text eligibility assessment. Upon detailed review, we excluded 388 articles for not meeting our specific inclusion criteria, resulting in 19 studies being included in the final review [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65]. Each of these 19 studies was accounted for in our report, ensuring a comprehensive and transparent documentation of our systematic review process, as shown in Figure 1.…”
Section: Eligibility Criteria For Screeningmentioning
confidence: 99%